Women in agriculture and climate risks: hotspots for development - Chanana, Nitya; Aggarwal, Pramod K.; Khatri-Chhetri, Arun (International Center for Tropical Agriculture, 2019)
Presented by Nitya Chanana (CCAFS), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.